Learning Basic Dance Movements Using The Drill And Practice Method For Students At Sanggar Brang Wetan Surabaya - Siti Nur Fitriati (Jurnal Pendidikan Sendratasik, 2025)
Learning basic dance movements is an important foundation for mastering dance skill, since it shapes movement technique, rhythmic sensitivity, and expressive appreciation. Sanggar Brang Wetan Surabaya applies the drill and practice method in teaching basic dance movements to help students master these skills through repeated, structured, and continuous exercise. This study aims to describe the implementation of the drill and practice method in learning basic dance movements and to describe the resulting learning outcomes of basic dance movement skills among students at Sanggar Brang Wetan Surabaya. The study draws on Hamalik's concept of the drill method, the behaviourist theories of Ivan Pavlov and John B. Watson, Benjamin S. Bloom's taxonomy of learning outcomes, and Anders Ericsson's concept of deliberate practice. A qualitative descriptive approach was used, with data collected through observation, interviews, and documentation involving the studio leader, two coaches, and student participants from the children's class, and analysed through data reduction, data display, and conclusion drawing, validated through method, source, and time triangulation. The results show that basic dance movement learning using the drill and practice method was implemented systematically through six stages: warming up, movement demonstration, movement imitation, repeated practice, correction, and movement refinement, delivered in a graded manner according to students' age and ability level. Learning outcomes show that students were able to master the wiraga, wirama, and wirasa aspects of dance well. Beyond technical mastery, basic movement learning also contributed to students' discipline, self-confidence, and readiness for the annual level-advancement examination. It is concluded that the drill and practice method is effective for teaching basic dance movement at Sanggar Brang Wetan Surabaya, as it helps students develop dance movement skills gradually, in a structured and sustainable manner that supports mastery of wiraga, wirama, and wirasa.